The Association Between Adiponectin Gene Polymorphism (rs1501299) and Metabolic Syndrome - Yin L; Tang Y; Yuan Y (Diabetes, Metabolic Syndrome and Obesity)
Lianli Yin,1 Yinghua Tang,2 Yulin Yuan1 1Department of Clinical Laboratory, Guangxi Academy of Medical Sciences, The People’s Hospital of Guangxi Zhuang Autonomous Region, Nanning, Guangxi, 530021, People’s Republic of China; 2Department of Clinical Laboratory, Guangxi Hospital of Traditional Chinese Medicine, The First Affiliated Hospital of Guangxi University of Chinese Medicine, Nanning, Guangxi, 530023, People’s Republic of ChinaCorrespondence: Yulin Yuan, Department of Clinical Laboratory, The People’s Hospital of Guangxi Zhuang Autonomous Region, Nanning, Guangxi, 530021, People’s Republic of China, Email yuanyulin@126.comObjective: To investigate the allelic genotypes of the adiponectin (APN) gene polymorphisms (rs1501299) and its association with APN level among Mets patients.Methods: A total of 410 patients with Mets and 203 healthy subjects were included in the study. The serum APN levels of the subjects were detected using enzyme-linked immunosorbent assay. The polymorphisms of the G/T gene at the rs1501299 locus of the APN gene were detected using restriction fragment length polymorphism polymerase chain reaction technology.Results: The serum APN levels were significantly lower in Mets patients than in the control group (15.0 ± 4.9 mg/L vs 27.2 ± 6.5 mg/L, p < 0.05). The distribution of the three genotypes at the rs1501299 locus was statistically different between the Mets patients and the control group (GG, GT, and TT, p < 0.05), and the frequencies of the T alleles were higher in the Mets patients than in control group (GT and TT, p < 0.05). Logistic regression analysis showed that the study subjects with the T allele had a higher risk of Mets than those with the G allele (OR = 1.85, p < 0.05). The risk of Mets was higher in GT and TT genotypes compared to in GG genotypes (OR = 1.43; OR = 2.14 vs OR = 1.00 ref). Similarly, it increased after combining GT and GG genotypes (OR = 1.73, p < 0.05). The APN levels in the GT (14.3 ± 5.3 mg/L) and TT (13.4 ± 5.4 mg/L) genotypes of the study subjects were lower than those of the GG genotype (15.5 ± 4.8 mg/L, p < 0.05).Conclusion: The occurrence of Mets may be associated with genetic variants at the rs1501299 locus, especially for individuals with G to T variants that reduce APN levels and lead to a higher risk of developing Mets.Keywords: adiponectin, gene polymorphism, metabolic syndrome